Analisis Efisiensi Biaya Overhead Pabrik Berdasarkan Anggaran Fleksibel: Studi Kasus pada UMKM di Kawasan Gerbang 1 Universitas Negeri Medan, Jalan Selamat Ketaren, Kenangan Baru. - Tuti Sriwedari; Karisa Kusumadewi Saputri; Marsha Astrid Exelsia Hutasoit; Nabila Hidayanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to analyze the efficiency of factory overhead costs using a flexible budget approach in small and medium enterprises (SMEs) located in the Gerbang 1 area of Universitas Negeri Medan, Jalan Selamat Ketaren, Kenangan Baru. The research focused on identifying the degree of efficiency and inefficiency in overhead cost management, particularly in response to fluctuations in production levels. This study emphasizes the importance of flexible budgeting as a managerial accounting tool that enables businesses to adjust cost expectations according to actual levels of activity, providing a more accurate evaluation of performance compared to static budgets. The research employed a qualitative approach with descriptive analysis. Data were collected through field observations and semi-structured interviews with five SME owners and two production employees in the food, beverage, and printing sectors. The study used purposive sampling to select participants with at least two years of operational experience and consistent production activities. Data analysis involved comparing actual factory overhead costs with flexible budget standards adjusted for actual production levels. The results were interpreted through thematic analysis to identify behavioral and managerial factors influencing cost efficiency. The findings revealed that most SMEs experienced inefficiencies in factory overhead costs ranging between 8–12% per month. The highest inefficiencies were found in electricity and indirect material costs due to lack of cost control and unplanned usage. However, maintenance and depreciation costs showed higher efficiency levels, supported by simple preventive practices. The application of a flexible budget provided significant insights into the evaluation of cost efficiency and managerial performance in SMEs. It not only served as a financial tool but also as a learning instrument for owners to understand cost behavior and make more informed decisions. The study recommends implementing flexible budgeting training and structured cost recording to enhance financial control and operational sustainability.